Hydrazine Hydrate as a Reagent for the Spectrophotometric Determination of Nickel(II) - Girish Kumar, K.; Muthuselvi, R. (Asian Journal of Chemistry, 2010)
A simple and rapid spectrophotometric method for the determination of nickel(II) is described. Nickel(II) complexes with hydrazine hydrate in the pH range of 7-10 with an absorption maxima of 585 nm and obeys Beer's law over a range of 2.5-8.0 μg mL -1 of nickel(II); the molar absorptivity of the species being 4.418 x 103 1 mor-1 cm-1. Interference from foreign ions has been studied along with the analysis of Ni(II) in alloys and industrial effluents.